Teacher’s Feedback on Learners’ English Writing Compositions - Hanisah Hanafi; Rivaldy Pomalingo; Yusna Bantulu (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
This study sought to investigate the progress of students writing skills on teacher’s written corrective feedback. This study followed a qualitative approach, using a descriptive research design. Using Hedge's (1998) theory on written correction indicators, three written essays were obtained via three stages of students' paper essays as the research data. All these received essays were then examined following Hedge’s theory, and the study report were built on the basis of the triple concurrent qualitative analysis postulated by Miles et al’s (2014). The findings of this study showed that out of three participants, participant 1 and participant 3 presented similar trends in terms of progress from teacher feedback on the writing, while participant 2 performed huge significant progress concerning teacher written feedback.